To solve the equation \( D(h) = 440 - 65h \) given \( h - 3 \frac{1}{2} \), let's clarify and solve this step-by-step.
-
First, we recognize that \( 3 \frac{1}{2} \) can be written as a decimal or improper fraction: \[ 3 \frac{1}{2} = 3.5 = \frac{7}{2} \]
-
It looks like you want to solve \( D(h) = 440 - 65h \) at \( h = 3.5 \). Therefore, we substitute \( h = 3.5 \) into the equation: \[ D(3.5) = 440 - 65(3.5) \]
-
Now calculate \( 65 \times 3.5 \): \[ 65 \times 3.5 = 227.5 \]
-
Substitute this back into the \( D(h) \) equation: \[ D(3.5) = 440 - 227.5 \]
-
Now perform the subtraction: \[ 440 - 227.5 = 212.5 \]
Therefore, the solution is: \[ D(3.5) = 212.5 \]